(untitled) (Transactions of the Association of European Schools of Planning, 2021)
Ecological and digital transitions alongside concerns over social inequalities have signalled the advent of complex new challenges for contemporary cities. These challenges raise issues pertaining to the dynamic capability of urban planners: more specifically, their ability to revise their tools and planning routines in urban projects. New paradigms of collective action for the transition towards innovative cities have been developed in large organisations. European companies, especially in public transportation, have developed such tools based on innovative design theories. One of these methodological tools, the Definition-Knowledge-Concept-Proposition (DKCP) process, was used to generate a new range of planning options for an urban district in Montreal, Canada. For many municipal organisations, the formulation of innovative ideas only concerns one stage of the process, represented by the ‘P’ phase. However, innovative routines should rather include the earlier phases of identifying the scope of possible innovations, the search for intriguing knowledge and disruptive design activities. The desire to tackle the complex challenges of 21st century cities has led to a new professional identity: the ‘innovative urban planner’.